Traumatic head injuries in children: demographics, injury patterns, and outcomes in Saudi Arabia - Hussin Albargi; Rayan Jafnan Alharbi; Ateeq Almuwallad; Naif Harthi; Yahya Khormi; Hari Krishnan Kanthimathinathan; Sharfuddin Chowdhury (International Journal of Emergency Medicine)
Abstract Background Traumatic head injuries (THIs) are among the leading cause of mortality and intensive care unit (ICU) admission in children worldwide. Most of the published literature concerning THIs arises predominantly from North America and Europe. However, only limited data about the incidence, characteristics and impact on children in Saudi Arabia exists. Methods We conducted a retrospective analysis of THIs in children (≤ 18 years of age) using data from the Saudi TraumA Registry (STAR) from August 2017 to December 2022. Data included patient demographic characteristics, the mechanism, type and severity of injury. We used multivariable logistic regression to assess the association between outcomes and clinical factors. Results We identified 466 children with THI. Most children were over six years of age (69.5%) and male (76.6%). Motor vehicle crashes (MVCs) were the most common cause of THIs (51.9%), with falls being more common in infants (69.8%). Over half of the children required ICU admission. Children with higher injury severity score, heart rate at presentation to the ED, hospital stay duration, respiratory assistance and need for surgery were more likely to require ICU admission. The overall mortality rate was 7.7%, with schoolchildren (age: 6–12 years) having the highest mortality rate (10.8%). Higher rates of ICU admission were associated with increases in the injury severity score (ISS), hospital stay duration, respiratory assistance and the need for surgery. Conclusions Children in the 6–12 year age-group had the highest mortality rate, reflecting high injury severities associated with increased ICU admissions. These findings highlight the importance of targeting preventive measures for MVCs in older children and improving trauma care for severe cases. Clinical trial number Not applicable.